The comparison of IGFBP-5 expression level in Pancreatic ductal adenocarcinoma tumors and their normal adjacent tissues - Jafar Karim Ghate; Parisa Tahmasebi; Ali Gheysarzadeh; Mina Jamalvandi (Egyptian Journal of Medical Human Genetics)
Abstract Background Insulin-like growth factor binding protein-5 (IGFBP-5) is one of the most important proteins playing a vital role in cellular processes such as proliferation, cell cycle regulation, cell death, and differentiation. Despite unremitting research, IGFBP-5 roles in pancreatic ductal adenocarcinoma (PDAC) have not been elucidated yet. The present study was designed to evaluate the expression of these proteins in PDAC tumors compared with their paired normal adjacent tissues. Here, pancreatic cancers of Iran’s national tumor bank were screened for suitable primary PDAC tumors. There are several inclusion and exclusion criteria to achieve suitable PDAC tumors. For instance, achieving both cancer and paired adjacent pancreatic normal tissues was the most inclusion criterion while chemotherapy, other pancreatic cancer (except PDAC), inflammatory diseases, and drug, and alcohol consumption are the main exclusion criteria. Finally, 60 tumors and 60 normal margins were chosen. The expression of IGFBP-5 using qRT-PCR was evaluated. Statistical analysis of Real-Time PCR analysis was done with the help of SPSS version 22 software and the significance level was set at P < 0.05. Results The results indicated that IGFBP-5 mRNA expression was reduced in PDAC tumors in comparison with normal margins. The expression level of this gene at the mRNA level in tumor samples was 0.72 ± 0.031 (Fold change was 1 in paired adjacent tissue). The results of the Paired t test showed that the level of IGFBP-5 mRNA in tumor samples showed a significant decrease compared to the adjacent normal pancreatic tissue (P < 0.05). Further investigations conducted on the samples showed that the amount of mRNA transcription changes for the IGFBP-5 gene in the first stage (Stage 0 + 1) was 0.85 ± 0.011, in the second stage was 0.79 ± 0.032 and in the last stage (Stage 3 + 4) was 0.62 ± 0.0813. The results of the One-way ANOVA statistical test showed that the decrease in transcription changes of the IGFBP-5 gene was significant in all stages (P < 0.05 for the first stage). In addition, there was a strong association between low expression of IGFBP-5 with clinicopathological features of PDAC (P < 0.05). Conclusion IGFBP-5 was down-regulated and its expression was associated with poor prognosis of PDAC.